GEOLOGY AND MODELING OF RESERVOIR BATUGAMPING FOR TACIPI FORMATION, FTH FIELD, SENGKANG SULAWESI, SOUTH SULAWESI - MUBINA , M.FATHAN
FTH Field is located in Sengkang Basin, the eastern part of South Sulawesi Province, with 154,3 km2 of area bordered by Walanae fault in the west, separating it from the West Sengkang Basin. The purposes of this study are to identify geological setting and the characteristics of limestone reservoir of Tacipi Formation, and calculate hydrocarbon in place reserve. The focus of the study is within the limestone reservoir interval of Tacipi Formation using well data and seismic data processed through seismic interpretation, depositional facies analysis, and petrophysical analysis. The processed data is then used in the modeling of facies and petrophysical properties. Based on well data, the stratigraphy of the study area, from the oldest to the youngest, consists of Camba Formation, Tacipi Formation, and Walanae Formation. The evolution of the basin is affected by the collision in the west of Sulawesi during Miosen until Pliocene, forming reverse faults in the west and east of FTH field. The limestone of Tacipi Formation is a gas-bearing reservoir deposited on isolated carbonate platform during Late Miocene, together with the subsidence of the basin during deposition. The reservoir is reef limestone which depositional facies is classified into reefal, reef debris, and lagoonal. Petrophysical analysis results in the average volume of shale as 21%, porosity as 24%, and water saturation as 54%. Volumetric gas reserve is calculated through the three areas penetrated by wells resulting in 276 BSCF of gas. The lead area is decided, located in the northern part of the study area with 456 BSCF of estimated reserve.